CLINICAL EXPERIENCE OF INTRODUCING MEDICAL ABORTION IN THE LATER STAGES IN THE REPUBLIC OF BURYATIA - Жамсоева, Ирина Базаровна; Алексеева, Лилия Лазаревна (Mother and Baby in Kuzbass, 2018)
Currently, the detection of many malformations of the fetus is possible only after 18-21 weeks. pregnancy, and so abortion at this time is forced, unavoidable, since some genetic diseases and congenital deformities in children is not compatible with life and are the cause of infant mortality. In other cases of malformations in children seriously affects the quality of life of both the child and the family. The problem of «safe» abortion in the later stages remains today one of the most urgent and difficult problems in obstetric practice. The aim of the study was to comparatively evaluate the effectiveness and complications of medical abortion for late term (22 week) using different schemes of combination of mifepristone in combination with misoprostol. Materials and methods.The study included 152 women of reproductive age to perinatal consultation on termination of pregnancy in the second trimester for medical indications in gynecology Department of SAHIRPC MZ RB for the period from 2015 to 2017, the Basic criteria for inclusion in the study was the pregnancy from 16 weeks before 22 weeks, absence of contraindications to medical abortion. The patients were divided into 2 groups according to regimens of mifepristone in combination with misoprostol. The results of the study. Expulse of the fetus and placenta occurred in 95,51 % (86/91) patients in the first group, 95,08 % (58/61) of women who received drugs according to the scheme 2. Conclusion. Mifepristone is bosonisation a drug with abortifacient effects, are identical at high and low dose. A lower dose of mifepristone does not increase the number of its complications. Optimal regimen for medical abortion: T. mifepristone 200 mg orally 24 hours so misoprostol 200 mcg vaginally with efficiency 95,08 %. These studies demonstrate a promising method to reduce complications and maternal mortality among women forced to terminate pregnancy in the second trimester.